PEMBERDAYAAN GURU SMPN 29 SATAP MALAKA DALAM PENYUSUNAN MEDIA LITERASI DIGITAL FLIPBOOK - Indah Lestari, Pertiwi; Aisyah, Sitti; Amalia Nur, Rizki (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Learning media in the era of digital disruption has become easier to access and organize. This condition demands adaptation and utilization of learning media that are relevant to technological advances. The facts are learning at SMPN 29 Satap Malaka still uses conventional textbooks, and not all teachers have utilized and created digital teaching media. This activity aims to improve teachers' knowledge and skills in developing and utilizing flipbook-based digital literacy which designed independently using flipbook. This activity consists of six stages:demonstration, program evaluation and program sustainability. The results of this PKM activity have a positive impact on participants (target partners), reviewed from the aspects of improving management and skills improvement aspects. The results of the analysis of participant response data to the implementation of training activities filled by 15 participants are in the very good category, namely the management aspect of 90.13% and the skills aspect of 89.11%. These results indicate that the response of participants is 100% in the good and very good categories, participants strongly agree that the socialization activity with training on compiling digital literacy media with flipbooks can improve their knowledge and skills in utilizing digital literacy in learning. The practicality of the activity can be seen from the observation sheet during the implementation of the activity, with an average of 98.83% in the very practical category, which means that the use of flipbook literacy media from this training is very practical to use as a learning medium.